PENGGUNAAN KATA "COMPUTER" DALAM FILM HIDDEN FIGURES (KAJIAN SEMANTIK) - Tasya Leksono Putri; Mia Rahmawati Yuwita (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2021)
A word can have different meanings depending on the use of the word itself, such as the word "computer" that shows in the Hidden Figures movie. It is important for us to know the meaning of a word itself to understand about the topic of a conversation. Thus, this research aims to analyze the use of the word "computer" and its meaning with semantic approach in Hidden Figures movie. Therefore, this study adopted a qualitative method. The data obtained were analyzed by emphasizing the search for meaning, understanding and concepts and descriptions of a phenomenon. The data collected is based on the conversations conducted by the characters in the Hidden Figures movie. The results of this study aim to show the use of the word "computer" and how it has meaning by referring to semantic studies.